Hukum Produk Cicil Emas di Bank Syariah Mandiri Ponorogo - Maulida Agustina; Khoirul Fathoni (Civiliza Publishing, 2023)
This study examines one of the products in Mandiri Islamic banks, namely gold installment products that use a murabaha contract. the problem is with the item, when the contract occurs, the object of the contract or gold is not owned by the independent Islamic bank and at the beginning of this contract there is a price discount agreed at the beginning of the contract when the customer pays off the installments at the beginning of the contract. The purpose of this study was to find out the law on murabahah contracts on gold installment products at Mandiri Syariah Bank Ponorogo and the law on murabahah repayment deductions on gold installment products at Mandiri Syariah Bank Ponorogo. This type of research is field research with descriptive analysis methods and data collection using observation, interviews and documentation. The results of this study are that the object of gold installment products at Mandiri Islamic banks using a murabaha contract is not in accordance with Islamic law which should be and the repayment deduction on the murabahah contract agreed upon at the beginning on gold installment products at Mandiri Islamic bank Ponorogo is also not in accordance with the DSN MUI fatwa No. 23 of 2002.